The benefits 0f “academic writing” course for the freshmen in English-medium-instruction departments in a Turkish State University - TOMAK, BURAK (My University, 2022)
The importance of academic writing is prevalent especially for the students taking English-medium instruction (EMI). After the intensive language lessons in the School of Foreign Languages, students must reach a certain level (B2) in order to pursue their academic studies in English. In addition to their departmental courses, freshmen in some EMI departments are offered “Academic Writing” course while some others do not have this opportunity. Thus, this study has tried to determine the efficiency and the benefits of this course for the freshmen in this university. For the purpose of the study, 5 freshmen that took “Academic Writing” course in the spring semester and 6 other freshmen who were not offered this course were assigned to write an academic essay on a given topic by the researcher. After the submission of their papers, the researcher had semi-structured interviews with each participant. Data were analyzed qualitatively via manual coding. It was found that the students who took “Academic Writing” course were more successful than their peers who were not given this opportunity in terms of grammar and vocabulary knowledge as well as the content formation in their academic papers.

Akademik yazmanın önemi, özellikle İngilizce eğitim alan öğrencilerin bölüm dersleri için açıktır. Yabancı Diller Yüksek Okulu’ndaki yoğun dil derslerinin ardından, bu öğrenciler İngilizce akademik çalışmalarını sürdürebilmeleri için belirli bir düzeye (B2) gelmek zorundadır. Bölüm derslerine ek olarak, İngilizce eğitim veren bazı bölümlerdeki birinci sınıf öğrencilerine “Akademik Yazım” dersi verilirken, bazıları bu fırsata sahip değildir. Böylelikle bu çalışma, bu dersin üniversite birinci sınıf öğrencilerine kazandırdığı etkinlik ve faydaları belirlemeye çalışmıştır. Araştırmanın amacı doğrultusunda, bahar döneminde “Akademik Yazım” dersini alan 5 birinci sınıf öğrencisi ve bu dersi almayan diğer 6 birinci sınıf öğrencisi, araştırmacı tarafından verilen bir konuda akademik bir makale yazmaları için görevlendirilmiştir. Araştırmacı, makalelerin gönderilmesinden sonra her katılımcıyla yarı yapılandırılmış görüşmeler yapmıştır. Veriler manuel kodlama yoluyla nitel şekilde analiz edilmiştir. “Akademik Yazım” dersini alan öğrencilerin, akademik makalelerindeki içerik oluşumunun yanı sıra gramer ve kelime bilgisi bilgileri açısından da bu dersi almayan akranlarına göre daha başarılı olduğu görülmüştür.
Bir Türk Devlet Üniversitesindeki İngilizce eğitim verilen bölümlerdeki birinci sınıf öğrencilerine sunulan “akademik yazım” dersinin faydaları
Keywords: Akademik Yazım; Birinci Sınıf Üniversite Öğrencileri; İngilizce Verilen Eğitim; İngilizce’nin Yabancı Dil Olarak Kullanıldığı Bağlam; Yükseköğretim; Dil Öğretimi; Academic Writing; Freshmen; English-Medium-Instruction; EFL Context; Higher Education; Language Teaching